2021
DOI: 10.1042/cs20210370
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding ion transport mechanisms in polycystic kidney disease

Abstract: This review focuses on the most recent advances in the understanding of the electrolyte transport-related mechanisms important for the development of severe inherited renal disorders, autosomal dominant (AD) and recessive (AR) forms of polycystic kidney disease (PKD). We provide here a basic overview of the origins and clinical aspects of ARPKD and ADPKD and discuss the implications of electrolyte transport in cystogenesis. Special attention is devoted to intracellular calcium handling by the cystic cells, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 143 publications
(209 reference statements)
0
10
0
Order By: Relevance
“…However, despite the availability of tolvaptan, there is still a strong demand for alternative therapeutic strategies as well as for new molecular targets for pharmacological intervention in ADPKD. One of the understudied pathogenic factors contributing to cyst growth is the abnormal ATP level reported in cystic fluid (Ilatovskaya et al, 2016; Sudarikova et al, 2021). We recently showed that in contrast to normal nephrons, the cystic epithelium exhibits excessive levels of pannexin‐1, a hemichannel capable of ATP release (Arkhipov & Pavlov, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the availability of tolvaptan, there is still a strong demand for alternative therapeutic strategies as well as for new molecular targets for pharmacological intervention in ADPKD. One of the understudied pathogenic factors contributing to cyst growth is the abnormal ATP level reported in cystic fluid (Ilatovskaya et al, 2016; Sudarikova et al, 2021). We recently showed that in contrast to normal nephrons, the cystic epithelium exhibits excessive levels of pannexin‐1, a hemichannel capable of ATP release (Arkhipov & Pavlov, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism by which this elevated Na + reabsorption by ENaC in renal tubules and endothelial cells causes kidney injury and fibrosis remain to be fully understood. Furthermore, ENaC dysfunction can promote renal fibrosis by facilitating the development of polycystic kidney disease (PKD), and the mechanism may be related to the elimination of antisecretory absorption and purinergic signaling regulation (Pavlov et al, 2015;Sudarikova et al, 2021). Although inhibition of ENaC such as amiloride is not a routine treatment for hypertension because of its lower efficacy compared to other diuretics, the refracted regulatory mechanism of ENaC in fibrosis cannot be ignored and may become a new tool in the treatment of renal fibrosis.…”
Section: Enacmentioning
confidence: 99%
“…There are several possible pathophysiological mechanisms of impaired kidney concentrating capacity in ARPKD, such as structural alteration of the distal tubules and collecting ducts due to cyst formation, alterations in vasopressin receptor (V2R), ion channels such as epithelial sodium channels (ENaC) or aquaporins (AQPR) [33].…”
Section: Age ( Years )mentioning
confidence: 99%